2017
DOI: 10.1371/journal.pone.0169331
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X Receptor Activation Attenuates Intestinal Ischemia Reperfusion Injury in Rats

Abstract: IntroductionThe farnesoid X receptor (FXR) is abundantly expressed in the ileum, where it exerts an enteroprotective role as a key regulator of intestinal innate immunity and homeostasis, as shown in pre-clinical models of inflammatory bowel disease. Since intestinal ischemia reperfusion injury (IRI) is characterized by hyperpermeability, bacterial translocation and inflammation, we aimed to investigate, for the first time, if the FXR-agonist obeticholic acid (OCA) could attenuate intestinal ischemia reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 48 publications
0
54
0
Order By: Relevance
“…II/R damage caused by bowel infarction, strangulation, severe hypotension, and shock is a frequent and clinically devastating condition with high morbidity and mortality. II/R can cause intestinal mucosal injury and ultimately lead to bacterial translocation, sepsis, multiple organ failure, and eventually death (Ceulemans et al, ; Goldsmith et al, ; Mallick, Yang, Winslet, & Seifalian, ). As mentioned above, apoptosis and inflammation are important mechanisms associated with II/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…II/R damage caused by bowel infarction, strangulation, severe hypotension, and shock is a frequent and clinically devastating condition with high morbidity and mortality. II/R can cause intestinal mucosal injury and ultimately lead to bacterial translocation, sepsis, multiple organ failure, and eventually death (Ceulemans et al, ; Goldsmith et al, ; Mallick, Yang, Winslet, & Seifalian, ). As mentioned above, apoptosis and inflammation are important mechanisms associated with II/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained in a rat model of intestinal I/R injury have recently demonstrated that pretreatment with OCA improves survival, preserves mucosal integrity, inhibits bacterial translocation and reduces pro-inflammatory cytokine release [ 58 ]. Our study provides novel insights into the effects of OCA by showing its capacity to increase MATE-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory pathological changes and IDO activation after AMI Mesenteric hypoperfusion could cause the damage of the intestinal vascular endothelial, the increase of intestinal epithelial permeability, and the gather of in ammatory mediators, as IFN-α,TFN-α,IL-1 [25][26][27]. Besides, as one of in ammatory cells, IDO could also signi cantly increased in a state of in ammation or infection [28].…”
Section: Mesenteric Ischemia After Amimentioning
confidence: 99%